TROUBLESHOOTING STUDENTS' SLOW LEARNING THROUGH CLASSICAL TUTORING SERVICE - Diandra Sutria Tatontos (Educouns Journal: Jurnal Pendidikan dan Bimbingan Konseling, 2020)
Solving the problem of learning difficulties of students who are slow to learn through guidance services is a form of guidance and counseling services that autonomy students in teaching and learning activities. This research was conducted using the action research method where there are two research cycles. The number of respondents was 20 junior high school students at Minahasa District. The research results showed that the learning problems experienced by students could be overcome